Getting a grip on insight: real-time and embodied Aha experiences predict correct solutions. Issue 5 (4th July 2021) - Laukkonen, Ruben E.; Ingledew, Daniel J.; Grimmer, Hilary J.; Schooler, Jonathan W.; Tangen, Jason M.
ABSTRACT: Insight experiences are sudden, persuasive, and can accompany valuable new ideas in science and art. In this preregistered experiment, we aim to validate a novel visceral and continuous measure of insight problem solving and to test whether real-time and embodied feelings of insight can predict correct solutions. We report several findings. Consistent with recent work, we find a strong positive relationship between Aha moments and accuracy for problems that demand implicit processing. We also found that the intensity of the insight experience further predicted the accuracy of solutions and participants naturally embodied the intensity of their insight experiences by squeezing the dynamometer more tightly. Intriguingly, this unintentional embodiment further predicted the accuracy of solutions. We suggest that the dynamometer complements previous measures by (1) simultaneously capturing both process and feeling in real-time, (2) highlights the value of measuring Aha moments on a continuum of intensity, and (3) firmly establishes that the impulsive feeling of Aha can carry information about the veracity of an idea. We discuss the findings in light of a recent theoretical account of how feelings of insight may act as a heuristic to select ideas from the stream of consciousness.